Determining key predictors influencing intention to use electric vehicles in Malaysia - Sang Y.-N.; Bekhet H.A. (IEEE Computer Society, 2023)
The purpose of this paper is to conduct an investigation into the key factors influencing the intention to use electric vehicles in Malaysia. An empirical study using a survey questionnaire distributed to a judgment sampling of 350 drivers within Selangor and Federal Territories (Kuala Lumpur and Putrajaya). A research model based on the framework of Theory of Planned Behavior was proposed to realize the objective of the study. Linear regression-stepwise technique was used to test the research hypotheses of this study. The result indicated that the intention to use electric vehicles in Malaysia can be explained by environmental concern, consumer knowledge, psychological benefitsand demographics. This paper is a useful source of information on the consumer intention for automotive players planning to market electric vehicles in Malaysia. It offers practical guidelines for formulation of marketing strategies that will address the real wants and needs of their future clients. Policy makers should address the appropriate intervention and policy to encourage the growth of electric vehicles in Malaysia as part of the strategy to increase energy efficiency and to reduce emissions and the reliance on fossil fuel within the transportation sector. Future study should be expanded to others cities to improve representation of respondents within Malaysia and more factors that might influence the intention to use to be further explored. © 2014 Asian Institute of Technology.